The application of Radon-222 in constraining zones of recent groundwater recharge in the Table Mountain Group aquifer in the City of Cape Town and its surrounding areas - Agyare-Dwomoh, Yaa (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.